1998
DOI: 10.5089/9781451921267.001
|View full text |Cite
|
Sign up to set email alerts
|

Opening Up and Geographic Diversification of Trade in Transition Economies

Abstract: This is a Working Paper and the author(s) would welcome any comments on the present text. Citations should refer to a Working Paper of the International Monetary Fund. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 5 publications
2
16
0
2
Order By: Relevance
“…Turning to the SEECs, Bulgaria and Romania experienced a strong rise in trade with the euro area between 1997 and 2003. The model suggests that trade links between Romania and the euro area are very strong already, thereby confirming the earlier results of Havrylyshyn and Al‐Atrash (1998). By contrast, Albania, Bosnia‐Herzegovina, Macedonia, and, to a lesser extent, Croatia still have significant leeway to intensify their trade with the euro area.…”
Section: Trade Effects Of the Eu Enlargementsupporting
confidence: 83%
See 1 more Smart Citation
“…Turning to the SEECs, Bulgaria and Romania experienced a strong rise in trade with the euro area between 1997 and 2003. The model suggests that trade links between Romania and the euro area are very strong already, thereby confirming the earlier results of Havrylyshyn and Al‐Atrash (1998). By contrast, Albania, Bosnia‐Herzegovina, Macedonia, and, to a lesser extent, Croatia still have significant leeway to intensify their trade with the euro area.…”
Section: Trade Effects Of the Eu Enlargementsupporting
confidence: 83%
“…Some transition economies were found to be much closer to equilibrium (this is the case for Hungary, with a ratio of potential to actual trade of 1.8), while countries like Romania and Albania, which did not participate in the Council of the Mutual Economic Assistance, started trade liberalization with regional trade structures closer to the gravity predictions estimated by Baldwin. Havrylyshyn and Al‐Atrash (1998) found that Romania achieved a significantly higher actual share of trade with the EU than predicted by the model in 1996. Kaminski et al.…”
Section: Empirical Methodology: the Gravity Modelmentioning
confidence: 77%
“…The literature so far explains hysteresis in former Soviet Union trade by remoteness and landlockedness 2 (Kaminski, Wang and Winters, 1996;Djankov and Freund, 2002;Grafe, Raiser and Sakatsume, 2005), poor access to markets and incomplete reforms (Havrylishin and Al-Atrash, 1998), weak institutions (Babetskaia- Kukharchuk and Maurel, 2004), poor product quality (e.g. Bevan et al, 2001), and hysteresis in consumption, production and business networks (Djankov and Freund, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The institutional reforms may favour trade redeployment to outside partners. Thus, those ‘which have made the most progress in structural reforms have also gone farthest in diversifying their exports to new destinations’ (Havrylyshyn and Al‐Atrash, 1998). Actually, transition reforms took place faster in the former Czechoslovakia and played an obvious role in the decline of bilateral trade between the Czech Republic and Slovakia.…”
Section: Discussionmentioning
confidence: 99%